Penanaman Nilai Moderasi Beragama pada Anak Usia Dini melalui Metode Pembiasaan - Maududi, Ahmad (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Religious moderation is an important value that needs to be instilled from an early age so that children are able to behave with tolerance, empathy, and responsibility in social interactions, and the habituation method is considered effective for cultivating character values through repeated direct experiences. This study aimed to instill the value of religious moderation in early childhood through the habituation method. The research employed Classroom Action Research (Penelitian Tindakan Kelas, PTK) using the spiral cycle model developed by Kemmis and McTaggart, consisting of two cycles with the stages of planning, action, observation, and reflection. The research subjects were 16 children aged 5–6 years at TK Daruttaqwa NW Aikmel Lombok Timur, comprising 6 boys and 10 girls. Data were collected through observation with direct monitoring, interviews, and documentation, and were analysed using descriptive statistics by calculating the percentage of achievement of success. The results showed an increase in the percentage of mastery of religious moderation, from an initial condition of 44% to 56% in cycle I and 86% in cycle II. These findings conclude that a consistently implemented habituation method, supported by teacher role modelling and parental cooperation, is effective in instilling the value of religious moderation in early childhood. The implications of this study underscore the importance of close collaboration between family and school so that children grow into individuals who are open, appreciative of differences, and able to live harmoniously in a plural society.